Critical Appraisal of Quality Improvement Publications in the Urological Literature. Issue 5 (26th September 2020) - Greenberg, Daniel R.; Sohlberg, Ericka M.; Shkolyar, Eugene; Shah, Jay B.
Abstract: Introduction: Quality improvement efforts enable rapid improvement in health care by measuring, analyzing and controlling the delivery of patient care. However, publications on quality improvement initiatives often vary in quality, decreasing their impact and restricting adoption by other institutions. We aim to compare the number, quality and trends of quality improvement publications in the urological literature. Methods: PubMed®/MEDLINE® and EMBASE® were used to identify relevant quality improvement publications in the urological literature since 1999. Critical appraisal of each publication was performed using the Quality Improvement Minimum Quality Criteria Set. Results: Inclusion criteria were met by 34 publications. Mean Quality Improvement Minimum Quality Criteria Set score ± SD was 10.8 ± 2.2 out of 16. Of the publications 44.1% (15) scored 10/16 or lower reflecting low quality. Only 8.8% (3) used the Standards for Quality Improvement Reporting Excellence. The majority of quality improvement publications consist of process rather than outcome or structural measures. The number of publications per year increased dramatically in 2015. However, average Quality Improvement Minimum Quality Criteria Set score before and after this time showed no change (p=0.88). Overall, 70.6% (24) of publications failed to report the quality improvement intervention's penetration/reach and 64.7% failed to report on a patient health related outcome. Conclusions: Critical appraisal of quality improvement publications in the urological literature indicates that the number of quality improvement publications is increasing over time. However, the reporting quality of quality improvement publications has stagnated. Adherence to reporting guidelines, quality standards and inclusion of all domains of the Quality Improvement Minimum Quality Criteria Set will potentially improve the quality of quality improvement publications and facilitate adoption of best practices in the field of urology.